Students’ perception of factors influencing graduate employability at a Higher Education institution in South Africa - Rukuni, T. F.; Woudberg, D.; du Preez, C.; Fourie, K.; Jute, S. (International Conference on Public Administration and Development Alternatives, 2018)
In recent years, South Africa has experienced an increase in the number of unemployed graduates while enrollment at institutions of higher learning is growing at a tremendous rate. Such a situation should be considered a worrying factor for both management and students at Higher Learning Institutions. Labour market specialists recommend that one of the most effective ways leading to employable graduates is through an assessment of employability factors within the academic curriculum and streamline the curriculum according to employer’s expectation. As previously noted, assessment of factors influencing employability of graduates within academic curriculum is rarely considered an issue of importance by management of Institutions of Higher Learning. The purpose of this study was to assess students’ perceptions of employability factors at an Institution of higher education and investigate how employability factors influence employment of graduates. A descriptive case study approach was conducted. A quantitative methodology, through which a structured questionnaire was used to collect data from a sample of at least 120 students at a private Institution of higher learning in Johannesburg, South Africa. SPSS was utilised to conduct descriptive and multivariate analyses including factor analysis, correlations, and regression analyses. Results indicated that, students had a negative perception towards graduate employability factors within the curriculum such as work attitudes, communication skills and exposure to the world of work. A positive correlation was also found to exist between factors affecting graduate employability and employment of graduates. Direction for future research was provided together with recommendations to management of the Institutions of higher learning. Keywords: Academic curriculum, Employability, Graduate employability, Institutions of Higher Learning
Article published in: The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Academic curriculum; Employability; Graduate employability; Institutions of Higher Learning; Employability; Students - Employment - Law and legislation